Preservation of Rifaiyah Values in the Community Life of Badak Village, Pemalang: Pelestarian Nilai-nilai Rifaiyah dalam Kehidupan Masyarakat Desa Badak, Pemalang - Irsyad, Mohammad Irsyad; Zahro, Zahida (Dharmahita: Journal of Community Service and Development, 2024)
Rifa'iyah, a religious-based community organization founded by KH. Ahmad Rifa'i from Kendal, Central Java, holds significant influence in Badak Village, Pemalang. This study aims to explore the efforts to preserve Rifa'iyah teachings in this village and identify the supporting and inhibiting factors. Employing a qualitative field research approach, data were collected through interviews, observations, and documentation, and analyzed using data reduction, data display, and conclusion drawing. Findings reveal that religious leaders and the community preserve Rifa'iyah teachings by consistently using and studying the Tarjumah book, maintaining Rifa'iyah traditions, developing educational institutions, promoting da'wah, and revitalizing the Rifa'iyah organization. Supporting factors include the ease with which laypeople accept Rifa'iyah teachings, strong community bonds, the commitment of religious leaders, and active community participation in religious studies. Inhibiting factors are the advancing tide of globalization, unregulated technology, and insufficient participation in organizational activities. These insights highlight the dynamic interplay of tradition and modernity in preserving Rifa'iyah values in Badak Village.